2013
DOI: 10.15506/jog.2013.33.5.113
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic alexandrites grown by the HOC method in Russia: internal features related to the growth technique and colorimetric investigation

Abstract: The estimated densities of the H 2 S phase (0.58 to 0.77g/cm 3) in isolated and fracture-bound multiphase inclusions in tanzanite have been used to model equilibrate and the contents will be lost through leakage and/or decrepitation. The internal pressures beyond which 'typical' microscopic inclusions in zoisite will leak (P d) but for larger inclusions (>100 μm) this value will be much lower. Thermophysical 10 μm) inclusions in zoisite would not survive the heating process to temperatures but the largest (c. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The Usambara effect and color change are two manifestations of the phenomenon of having two distinct transmission windows in the visible spectrum. This study quantitatively described the interplay between color change and the Usambara effect (Schmetzer et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The Usambara effect and color change are two manifestations of the phenomenon of having two distinct transmission windows in the visible spectrum. This study quantitatively described the interplay between color change and the Usambara effect (Schmetzer et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…Liu et al (1999b) suggested that this tourmaline should only be considered a color-change stone within a certain range of path lengths. Schmetzer et al (2013) studied a synthetic alexandrite crystal and analyzed the relationship between the "alexandrite effect" and the Usambara effect in this pleochroic mineral with varying thickness. To shed more light on this phenomenon, we have carried out a detailed quantitative study of the influence of path length on color difference and hue angle difference under both lighting conditions for three different garnets.…”
mentioning
confidence: 99%
“…1). Note that the Usambara effect was recently also established on Tanzanian gem-quality chromium-and vanadium-bearing garnets of spessartine-pyrope composition (Krzemnicki, 2014) and in some types of synthetic alexandrite (Schmetzer et al, 2013).…”
Section: Introductionmentioning
confidence: 92%